Electricity generation and demand flexibility in wastewater treatment plants: Benefits for 100% renewable electricity grids. (15th June 2020) - Ali, Syed Muhammad Hassan; Lenzen, Manfred; Sack, Fabian; Yousefzadeh, Moslem
Highlights: Wastewater treatment plants provide energetic flexibility in a renewable grid. Wastewater treatment plant's dispatchable power generation can plug supply gaps. Mapping electricity demand and generation on 90 × 110 GIS grid for Australia. Renewable electricity grid of 149 GW is possible at 16 ¢/kWh and 28% capacity factor. Abstract: In future, the low carbon electricity grid will need an additional potential of energetic flexibility to compensate the variable renewable supply. Wastewater treatment plants have the potential to provide electricity demand and generation flexibility. A novel approach of utilising the energetic flexibility in wastewater treatment plants to optimize the installed capacity of a fully renewable electricity grid in Australia is presented. In this hourly electricity supply simulation, both the electricity generation and demand of wastewater treatment plants are shifted for reducing the required size of 100% renewable electricity grid and achieving perfect supply-demand matching. The electricity demand and dispatchable electricity generation capacity of cogeneration systems in wastewater treatment plants are modelled on a 90 × 110 raster grid. For a 6-hour shift in wastewater treatment plant's electricity demand and it's electricity generation limited to five times the current capacity, a 100% renewable electricity grid would need an installed capacity of around 149 GW to meet the existing reliability standard (6–8 h of power outages per year). The electricity generation cost is around 16 ¢/kWh with a capacity factor of 28% and spilt electricity of less than 21%. The electricity generated from sewage methane in wastewater treatment plants is only 1% of the total generation and is utilised along with biomass power plants to plug demand-supply gaps. Our results indicate that a 2% reduction in installed capacity and 11% reduction in levelized cost of electricity is achieved by utilizing the energetic flexibility of wastewater treatment plants.